Reliability Index Assessment-Section Technique pada Distribusi Listrik Penyulang Suci Menggunakan Software ETAP - Haz, Fauzia; Arya Mustopa; Giri Angga Setia; Dede Furqon; Atik Charisma; M. Reza Hidayat (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2024)
Problems that often occur with electricity distribution network quality, continuity and availability services consumers. Study aims evaluate reliability of the 20 kV medium-voltage electricity distribution system at the Suci ULP Garut Kota feeder, where 2021 Suci feeder experienced 14 disturbances duration 791 minutes (13.1 hours), including a medium-voltage overhead line that broke 2 Phase. Determining the reliability index value electricity distribution system of the Kudus ULP Garut City feeder, mathematical calculations were carried out using RIA-section technique predetermined formula and simulated using ETAP software with study case reliability assessment. Based on the results of the study, improvement was made that the reliability value feeder was stable. Repairs were carried out 2 times, first repair, 2 fuse cutouts were installed and 4 transformers were moved, while the second repair was to divide the Suci feeder into 2 parts, namely the western Suci feeder and the eastern Suci feeder. So making these improvements the reliability index Suci feeder becomes stable and meets what has been SPLN 68-2: 1986, which is below SAIFI 3.3 times/customer/year and SAIDI 21.9 hours/customer/year.